Birthplace in Australia: Antenatal preparation for the possibility of transfer from planned home birth. (November 2018) - Fox, Deborah; Sheehan, Athena; Homer, Caroline SE
Highlights: Back-up hospital bookings reduce uncertainty for all concerned in the event of transfer. Women found it helpful to feel open to the possibility, prior to a transfer. Feeling open to transfer during pregnancy involved seeking information and exploring feelings. Homebirth midwives fostered professional connections with hospitals, to enhance collaboration. Abstract: Objective: The aim of the study was to explore how women and midwives prepare, during the antenatal period, for the possibility of intrapartum transfer from planned home birth. Design: A Constructivist Grounded Theory approach was taken in order to focus upon the social interactions and processes that emerged. Setting: Urban and regional areas in four states of south eastern Australia. Participants: Thirty-one semi-structured interviews were conducted with women and midwives. Findings: There were three sub-categories relating to preparation for the possibility of transfer. These were 'Building the midwife–woman partnership', 'Fostering professional connections' and 'Reducing uncertainty'. The reciprocal trust inherent in the midwife–woman partnership helped women feel safe in relation to the possibility of intrapartum transfer to hospital. Midwives who had positive transfer experiences spoke about their commitment to fostering professional connections with hospitals and health professionals as a part of building the capacity for collaboration if, and when, a transfer occurred. Reducing uncertainty involved preparation that included not only providing information and emotional support to the woman around the possibility of transfer, but also arranging for her to book in to a back-up hospital.